1989
DOI: 10.1159/000129019
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenal Graft in the Rat: An Original Microsurgical Technique

Abstract: The authors describe an original surgical technique for pancreatic transplantation carried out on an experimental rat model which duplicates as closely as possible the anatomic-functional situation of a pancreatic graft in man (one arterovenous vascular peduncle with one functioning kidney only). The technique entails a microanastomosis between the mesenteric artery and the portal vein of the donor organ with the left renal artery and vein of the recipient. This method appears to be technically encouraging and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Because ex vivo reperfused models [23] show no physiological regulation of perfusion, they do not seem to be suitable for microcirculatory investigations. In models of pancreatic transplantation [24], immunological reactions can also influence the changes induced by ischemia/reperfusion injury. Models of in situ ischemia/reperfusion of the pancreas where the ischemia is induced by clamping only the main supplying vessels [19,25] do not allow flushing of the pancreatic tail-segment before ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Because ex vivo reperfused models [23] show no physiological regulation of perfusion, they do not seem to be suitable for microcirculatory investigations. In models of pancreatic transplantation [24], immunological reactions can also influence the changes induced by ischemia/reperfusion injury. Models of in situ ischemia/reperfusion of the pancreas where the ischemia is induced by clamping only the main supplying vessels [19,25] do not allow flushing of the pancreatic tail-segment before ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…e �ve-year patient, pancreas, and kidney survival aer SPK transplantation in this series are 94%, 77%, and 89%, respectively. is compares favourably with United States data in which �ve-year patient and pancreas-gra survival rates were 87% and 71-73%, respectively, for patients who received a SPK transplant [26,27].…”
Section: Discussionmentioning
confidence: 63%
“…Continuing research in microsurgery has considerably expanded experimental surgery and given new impulses to clinical surgery [1][2][3][4] . Whole-organ pancreas transplantation in the rat was first described by Lee et al [3,4] in 1972.…”
mentioning
confidence: 99%
“…Simultaneous en bloc pancreaticoduodenal kidney transplantation is being applied with increasing frequency in the treatment of diabetes mellitus type I and selected cases of type II [5][6][7][8] . A review of the literature of isolated pancreas transplantation in rat models showed that different techniques or modifications can be applied [2,4,9,[11][12][13] . However, pancreas transplantation in the Key Words Transplantation ؒ Pancreas ؒ Kidney ؒ Allograft ؒ Surgical technique ؒ Rat model Abstract Background: For experimental basic research, standardized transplantation models reflecting technical and immunologic aspects are necessary.…”
mentioning
confidence: 99%